APPLICATION OF ACTIVE LEARNING MODEL TYPE TEAM QUIZ ON SOCIOLOGY SUBJECTS - Firmansyah, Eja; Okianna, Okianna; Ramadhan, Iwan (International Journal of Learning and Instruction (IJLI), 2025)
The aim of this research is to find out how the planning, implementation and results of implementing the Team Quiz Type Active Learning learning model in the sociology subject of class XI IPS at MA Yasti Sekura are carried out. The method used in this research is a qualitative research method with a descriptive research form. The data sources in this research are one sociology teacher who teaches at MA Yasti Sekura and four students in class XI IPS MA Yasti Sekura. The results of this research show that in lesson planning teachers make lesson plans, prepare materials and make homework assignments. In implementing learning, the teacher carries out learning activities in accordance with the RPP that has been created, namely consisting of initial, core and final activities. The implementation of the Team Quiz Type Active Learning learning model obtained learning outcomes consisting of knowledge domains with assessments based on homework assignments with an average score of 87.6. In the attitude domain there are values of activeness, discipline, mutual cooperation, politeness and self-confidence. The domain of skills obtained by students is from how to express opinions, ask questions and answer. The application of the Team Quiz Type Active Learning learning model creates a very active class atmosphere where students dominate the learning process so that general problems such as boredom and sleepiness felt by students can be resolved, besides that, the application of the Team Quiz Type Active Learning learning model makes the class atmosphere more comfortable. It's fun because in its implementation there is a quiz game between groups